Contribution to pathogenesis of accessory proteins of deadly human coronaviruses - Hurtado-Tamayo, Jesus; Requena-Platek, Ricardo; Enjuanes, Luis; Bello-Perez, Melissa; Sola, Isabel (Frontiers in Cellular and Infection Microbiology, 2023)
Coronaviruses (CoVs) are enveloped and positive-stranded RNA viruses with a large genome (∼ 30kb). CoVs include essential genes, such as the replicase and four genes coding for structural proteins (S, M, N and E), and genes encoding accessory proteins, which are variable in number, sequence and function among different CoVs. Accesory proteins are non-essential for virus replication, but are frequently involved in virus-host interactions associated with virulence. The scientific literature on CoV accessory proteins includes information analyzing the effect of deleting or mutating accessory genes in the context of viral infection, which requires the engineering of CoV genomes using reverse genetics systems. However, a considerable number of publications analyze gene function by overexpressing the protein in the absence of other viral proteins. This ectopic expression provides relevant information, although does not acknowledge the complex interplay of proteins during virus infection. A critical review of the literature may be helpful to interpret apparent discrepancies in the conclusions obtained by different experimental approaches. This review summarizes the current knowledge on human CoV accessory proteins, with an emphasis on their contribution to virus-host interactions and pathogenesis. This knowledge may help the search for antiviral drugs and vaccine development, still needed for some highly pathogenic human CoVs.